KOMUNIKASI INTERPERSONAL KEPALA DESA DALAM MEMBINA GENERASI MUDA - Hasan Abdul Wafi; Isfironi; Yohandi (Maddah : Jurnal Komunikasi dan Konseling Islam, 2020)
Interpersonal communication is communication between individuals face to face that allows each participant to capture the reactions of others directly or indirectly. The purpose of this study was to describe the interpersonal communication model of the Village Head in fostering the younger generation in Perante village, Asembagus subdistrict, Situbonso district and describing the effect of interpersonal communication of the Village Head in fostering the younger generation in Perante village, Asembagus, Situbonso district. This research uses descriptive research and qualitative research approaches. The presence of researchers as observers (observers) as well as data collectors through interviews and documentation. The results showed that the interpersonal communication model carried out by the Village Head was a linear model, an interactive model, and a transactional model. The effect obtained is expressing attention to others, finding yourself, discovering the outside world, building and maintaining harmonious environment, influencing attitudes and behavior.